Point Pleasant. The complete series [videorecording (DVD)] - McLaughlin, John J.; Noxon, Marti, 1964-; Harnois, Elisabeth, 1979-; Show, Grant, 1962-; Page, Samuel, 1976-; Dollar, Aubrey, 1980-; Meyer, Dina, 1968-; Richardson, Cameron, 1979-; Weber, Brent, 1980-; Walters, Susan, 1963-; Burgi, Richard, 1958-; Duncan, Robert; et al. (20th Century Fox Home Entertainment, 2005)
A series of supernatural events begin in a small coastal New Jersey town after the arrival of a mysterious teenage girl who apparently has ability to make people and events act on her behalf.